Resistance of Rc Annular Cross-Sections With Openings Subjected to Axial Force and Bending - M. LECHMAN (Engineering Transactions)
This paper presents ultimate limit state analysis of the resistance of reinforced concrete (RC) annular cross-sections with openings, subjected to the axial force and the bending moment. Based on nonlinear material laws for concrete and reinforcing steel and using the method of mathematical induction, analytical formulae are derived in the case when the cross-section is weakened by an arbitrary number of openings located symmetrically with respect to the bending direction. In this approach, the additional reinforcement at openings is also taken into account. The results of numerical calculations are presented in the form of interaction diagrams with the design values of the normalized cross-sectional forces nu and mu for the sections weakened by openings as well as for the closed ones. This approach has been applied to investigate the influence of different parameters such as the size and the number of openings, the reinforcement ratio, the additional reinforcement at the opening, the form of stress-strain relationships for concrete and the thickness/radius ratio, on the section resistance.